Efforts to Improve the Ability to Memorize Juz 30 through Illustrated Juz Amma Books for Children at Ra Ar Raihan Bantul - Untari (Jurnal Profesi Guru Indonesia, 2024)
This study aims to improve the ability to memorize Juz 30 in children through the media of illustrated Juz Amma books in group B children at RA Ar Raihan Bantul in semester 1 of the 2021/2022 Academic Year. This research is a Classroom Action Research with research procedures including planning, implementation, observation and reflection. The research consists of 2 cycles, the subjects of the research are children in group Bdi RA Ar Raihan Bantul in semester 1 of the 2021/2022 Academic Year. The object of the research is the ability to memorize Juz 30, which is observed through a video simulation of learning improvement. Data is obtained from observations, namely reflection sheets. Data analysis is carried out using narrative-qualitative analysis. The results of the analysis of the learning improvement simulation, the advantages carried out by the teacher are the use of illustrated Juz Amma book media, so that children are interested in participating in memorizing Juz 30. While the weaknesses carried out by the teacher are less cheerful facial expressions, unclear/detailed delivery of assignments. Based on this analysis, it can be concluded that memorizing activities using illustrated Juz Amma books can improve children's memorization skills at RA Ar Raihan Bantul in Semester 1 of the 2021/2022 academic year.